Associations between allelic polymorphism of the BMP Binding Endothelial Regulator and phenotypic variation of cattle. Issue 6 (December 2015) - Zhao, Chunping; Gui, Linsheng; Li, Yaokun; Plath, Martin; Zan, Linsen
Abstract: The BMP Binding Endothelial Regulator (BMPER) is an inhibitor of bone morphogenetic proteins (BMPs), which play fundamental roles in adipocyte differentiation, fat development and energy balance. The objectives of this study were to detect polymorphisms of BMPER gene in four indigenous Chinese cattle populations and to investigate their effects on body size traits. Initially, three SNPs, namely G100597A (SNP1), C105331A (SNP2), and G105521A (SNP3) and eight distinct haplotypes were identified. In a total of 12 SNP-SNP combinations, SNP2-SNP3 had a strong linkage in Qinchuan cattle. These four cattle populations belong to intermediate genetic diversity at three SNP loci except Shuxuan cattle population in SNP3. At SNP1, genotype AA was associated with an increased body size. For SNP2, the heterozygous genotype individuals had a greater rump length than those of two other homozygotic genotypes. At SNP3, individuals with GG genotype had smaller rump length and hip width. A total of seven haplotype combinations were detected in Qinchuan cattle population and association analysis results showed individuals with Haplotype combination 4/2 (AAA/CAA) had greater rump length than those with Hap3/1 and Hap3/3 (P < 0.05). These results strongly suggest that bovine BMPER gene may be used as a genetic marker for cattle breeding. Highlights: Three SNPs and eight haplotypes were identified in the bovine BMPER gene. Some genotypes of these SNPs were associated with the body sizes of Qinchuan cattle. Cattle with Haplotype combination 4/2 (AAA/CAA) had greater rump length than those with Hap3/1 and Hap3/3. We proposed that bovine BMPER gene can be used as a genetic marker for cattle breeding.